High and Highly Variable Spontaneous Mutation Rates in Daphnia. (10th June 2020) - Ho, Eddie K H; Macrae, Fenner; Latta, Leigh C; McIlroy, Peter; Ebert, Dieter; Fields, Peter D; Benner, Maia J; Schaack, Sarah
Abstract: The rate and spectrum of spontaneous mutations are critical parameters in basic and applied biology because they dictate the pace and character of genetic variation introduced into populations, which is a prerequisite for evolution. We use a mutation–accumulation approach to estimate mutation parameters from whole-genome sequence data from multiple genotypes from multiple populations of Daphnia magna, an ecological and evolutionary model system. We report extremely high base substitution mutation rates (µ - n, bs = 8.96 × 10 −9 /bp/generation [95% CI: 6.66–11.97 × 10 −9 /bp/generation] in the nuclear genome and µ - m, bs = 8.7 × 10 −7 /bp/generation [95% CI: 4.40–15.12 × 10 −7 /bp/generation] in the mtDNA), the highest of any eukaryote examined using this approach. Levels of intraspecific variation based on the range of estimates from the nine genotypes collected from three populations (Finland, Germany, and Israel) span 1 and 3 orders of magnitude, respectively, resulting in up to a ∼300-fold difference in rates among genomic partitions within the same lineage. In contrast, mutation spectra exhibit very consistent patterns across genotypes and populations, suggesting the mechanisms underlying the mutational process may be similar, even when the rates at which they occur differ. We discuss the implications of high levels of intraspecific variation in rates, the importance of estimating gene conversion rates using a mutation–accumulation approach, and the interacting factors influencing the evolution of mutation parameters. Our findings deepen our knowledge about mutation and provide both challenges to and support for current theories aimed at explaining the evolution of the mutation rate, as a trait, across taxa.